THE PRINCIPLE OF PUBLICITY OF THE NATIONAL NORMATIVE ACTS. LEGAL EFFECTS - Iulia , BOGHIRNEA (International Journal of Legal and Social Order, 2022)
In this paper, we want to identify the general rule regarding the moment when the legal norm enters into force: the moment of publication of the normative act in the official gazette or three days after bringing the normative act to public knowledge through publication?In the following we will investigate what emerges from the spirit of the legal norms in the matter.